The CopenHeartSF trial—comprehensive sexual rehabilitation programme for male patients with implantable cardioverter defibrillator or ischaemic heart disease and impaired sexual function: protocol of a randomised clinical trial - Johansen, Pernille Palm; Zwisler, Ann-Dorthe; Hastrup-Svendsen, Jesper; Frederiksen, Marianne; Lindschou, Jane; Winkel, Per; Gluud, Christian; Giraldi, Annamaria; Steinke, Elaine; Jaarsma, Tiny; Berg, Selina Kikkenborg (BMJ Open, 2013)
Introduction Sexuality is an important part of people’s physical and mental health. Patients with heart disease often suffer from sexual dysfunction. Sexual dysfunction has a negative impact on quality of life and well-being in persons with heart disease, and sexual dysfunction is associated with anxiety and depression. Treatment and care possibilities seem to be lacking. Studies indicate that non-pharmacological interventions such as exercise training and psychoeducation possess the potential of reducing sexual dysfunction in patients with heart disease. The CopenHeartSF trial will investigate the effect of a comprehensive sexual rehabilitation programme versus usual care. Methods and analysis CopenHeartSF is an investigator-initiated randomised clinical superiority trial with blinded outcome assessment, with 1:1 central randomisation to sexual rehabilitation plus usual care versus usual care alone. Based on sample size calculations, 154 male patients with impaired sexual function due to implantable cardioverter defibrillator or ischaemic heart disease will be included from two university hospitals in Denmark. All patients receive usual care and patients allocated to the experimental intervention group follow a 12-week sexual rehabilitation programme consisting of an individualised exercise programme and psychoeducative consultation with a specially trained nurse. The primary outcome is sexual function measured by the International Index of Erectile Function. The secondary outcome measure is psychosocial adjustment to illness by the Psychosocial Adjustment to Illness Scale, sexual domain. A number of explorative analyses will also be conducted. Ethics and dissemination CopenHeartSF is approved by the regional ethics committee (no H-4-2012-168) and the Danish Data Protection Agency (no 2007-58-0015) and is performed in accordance with good clinical practice and the Declaration of Helsinki in its latest form. Registration Clinicaltrials.gov identifier: NCT01796353 .